Usos da liberdade e agonismo em Michel Foucault - Dotto, Pedro Mauricio Garcia (2016)
The current work aims to comprehend the problematic of freedom in Michel Foucault’s thought in its co-relation to power, ethics and resistance. To achieve this purpose, the concept of “agon” and “agonism” that the philosopher elaborate will be used as an interpretative key to apprehend what we could understand as an “aporia of freedom” in his theoric production ; that is to say freedom as condition of existence of power and freedom as ontological condition of ethics. In this sense, his consideration about resistance will also be of great importance for the development of our research